2018
DOI: 10.1007/s11121-018-0894-5
|View full text |Cite
|
Sign up to set email alerts
|

Novel Methods for Screening: Contributions from Attachment and Biobehavioral Catch-up

Abstract: Preventative interventions are needed across the lifespan, including for children who have experienced maltreatment. However, interventions' effect sizes are typically smaller in real-world settings than in clinical trials. Identifying providers who are likely to implement interventions with fidelity could promote implementation outcomes through targeted allocation of training resources. This study tested two pre-training screening measures as predictors of provider fidelity to Attachment and Biobehavioral Cat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 40 publications
1
14
0
Order By: Relevance
“…Our findings suggest that provider education had little impact on training engagement and outcomes. They are consistent with those of other studies finding small or no associations between provider education and EBT delivery‐related outcomes, 38‐41,64,65 as well as studies finding advantages for providers without advanced degrees 42,45 . This study extends earlier work by using equivalence testing to answer this question in a large sample of providers delivering services to children and families.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Our findings suggest that provider education had little impact on training engagement and outcomes. They are consistent with those of other studies finding small or no associations between provider education and EBT delivery‐related outcomes, 38‐41,64,65 as well as studies finding advantages for providers without advanced degrees 42,45 . This study extends earlier work by using equivalence testing to answer this question in a large sample of providers delivering services to children and families.…”
Section: Discussionsupporting
confidence: 90%
“…For example, providers with more advanced degrees have been found to exhibit more competence in some studies, 36,41 but less competence in others 37 . One study found that providers without advanced degrees had greater adherence to a manualized intervention than those with advanced degrees, 42 while other research has found no associations between provider education and skills or fidelity in mental health and child welfare interventions 38‐40,43,44 . Within child mental health specifically, a meta‐analysis of treatment outcome research found that providers without advanced degrees were more effective than professional or student providers, although effects differed by patient age, gender, and problem type 45 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Suitability to be a parent coach was determined regardless of professional and educational background and based on selection criteria defined by the model developer: (a) evidence of valuing attachment/openness (as assessed via an abbreviated attachment interview) and (b) initial skill in delivering in-the-moment feedback on parent–child interactions (as assessed via a video vignette-based role-play; Caron, Roben, Yarger, & Dozier, 2018). Parent coaches participated in a 2-day training followed by a year of weekly supervision provided by the model developer's team.…”
Section: Methodsmentioning
confidence: 99%
“…This solution was not inevitable -priority could have been given to testing abbreviated versions of measures (e.g. Caron et al, 2018, using a cut-down AAI) decades earlier. Dependence on an oral culture risks certain in-group dynamics and assumes the inevitability of a small possible number of credible developmental attachment researchers.…”
Section: Adjustmentsmentioning
confidence: 99%